Surgical Treatment of Bilateral Bullous Exudative Retinal Detachment Following Systemic Corticosteroid Therapy: A Case Report from Aceh - Lia Meuthia Zaini (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Exudative retinal detachment refers to elevation of the neural retina caused by subretinal fluid accumulation in the absence of a retinal break or significant preretinal traction. Management of exudative retinal detachment should include management of the underlying disease. When the fluid is not resolved, surgical intervention is planned after failure of conventional treatment. We demonstrated the successful surgical management of exudative bullous retinal detachment using the internal drainage technique. Case Presentation: A 45 years old man presented with complaint of blurred vision since 5 months before admission. Worsening occurred mainly after administration of high dose methylprednisolone infusion therapy. Visual acuity of the right eye was hand motion, and left eye was 1 meter finger counting. Fundus examination revealed exudative bullous retinal detachment in both eyes. Discussion: Surgery can be considered as a treatment of choice for exudative retinal detachment if medical management is unsuccessful. A complete examination to determine the cause of the disease is needed before carrying out surgery. External and internal drainage techniques have been reported to be successful in managing subretinal fluid in chronic exudative retinal detachment. We chose vitrectomy with internal drainage because large amount of dense subretinal fluid can make transscleral drainage very difficult. Conclusions: Surgical management (vitrectomy with internal drainage) can provide good results in chronic exudative retinal detachment, but should not be used as first-line therapy.